A kinetic and kinematic comparison of the grab and track starts in competitive swimming - Juergens, C. A.; Rose, D. J.; Smith, G. A.; Calder, C. A. (Medicine & Science in Sports & Exercise, 1999)
In competitive swimming a spread in time of only 0.10, and 0.16 seconds constituted the difference between finishing second and seventh, and first and eighth, respectively, in the women's 50 yard freestyle at the 1993 NCAA Division III National Swimming & Diving championships. Based on data collected over a period of years Maglischo (1993) noted that "improving the start can reduce race times by at least 0.10 second" (p. 544). Therefore it is beneficial to the outcome of a race to direct attention to maximizing the effectiveness of the racing start. The primary purpose of this study therefore was to compare kinetic and kinematic components of the grab and track style starts. During the past two decades extensive kinematic research has been done using cinematography. These studies used time, velocity, displacement, and the measure of angles (i.e. at takeoff and entry) to measure the relative effectiveness of various racing starts. Conversely, there has been limited analysis of racing starts using kinetic measurements. Four kinetic and five kinematic variables were evaluated in this study to compare the relative effectiveness of the starting techniques. Ten female varsity swimmers, who had used both starts interchangeably in competition, were selected for this study. Force components were obtained directly from a Kistler force platform. Block time, horizontal and vertical impulse, and average horizontal and vertical force values were obtained in subsequent analysis of the Force-time data. Each subject was videotaped as she executed three trials of each start. The video data were digitized and then analyzed using two dimensional video analysis techniques. The type of start technique used on each trial was randomly ordered. Kinematic variables of horizontal and vertical displacement of the center of mass, average horizontal velocity and vertical velocity were also obtained from the video data in order to determine which of the two starting techniques (i.e., grab vs. track) was the most effective. 2 x 10 (starting technique x subject) repeated measures Analyses of Variance indicated significant differences (p < 0.01) between the starting styles for five of the nine dependent variables measured which provided support for the original contention that the track style start was the more effective of the two racing start techniques investigated. The results of this study provide support to the empirical and observational findings of earlier researchers.